Islamic Religious Education in Inclusive Education: Curriculum Modification for Slow Learner Students at SMP Muhammadiyah 1 Godean - Difaul Husna; Yazida Ichsan; Unik Hanifah Salsabila (International Journal on Advanced Science, Education, and Religion, 2021)
Education for children with special needs began to change on the basis of diversity and the fulfillment of the right to obtain an education and an inclusive education. Inclusive educators enforce learning in the same learning environment for each student, for regular students or students with special needs, including for slow learners. This qualitative descriptive research was conducted with the intention of knowing the implementation of Islamic Religious Education curriculum in the setting of inclusive education, namely at SMP Muhammadiyah 1 Godean. The research subjects were obtained through purposive sampling method, with research data obtained through observation methods, interviews and documentation. Data analysis is carried out through several procedures, namely data reduction, data presentation, verification and data validity test using triangulation techniques. The results showed that Islamic Education learning was carried out in regular full inclusion classes using a modified regular curriculum for slow leaner students. Learning Islamic Religious Education SMP Muhammadiyah 1 Godean faced several separate problems such as the un availability of Special Companion Teachers and differences in characteristics of each student, both regular students and special needs. Keywords: Inclusive Education, Students Special Needs, Islamic Education